Pengaruh Penggunaan Laboratoium Virtual Dalam Pembelajaran Inkuiri Terbimbing Terhadap Penguasaan Konsep Kalor Peserta Didik - Hermansyah Hermansyah; Gunawan Gunawan; Ahmad Harjono (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2017)
The purpose of this study is to examine the effect of using virtual laboratory in guided inquiry learning on studentsÃ¢â¬â¢ mastery concept of heat material.ÃÂ  This study is quasi experiments with posttest only control group design. There were 58 respondents in this study which were divided into two group; experimental group and control group. The data were analyzed by using t-test. The results showed that experimental groupsÃ¢â¬â¢ mastery concepts significantly differed from the control group. It can be concluded that the use of virtual laboratory in guided inquiry learning model affects studentsÃ¢â¬â¢ mastery concepts of heat material.